A cross-cultural comparison of talent identification and development in Paralympic Sports. Perceptions and opinions of athletes, coaches and officials - Radtke, S.; Doll-Tepper, G. (Sportverlag Strauß, 2014)
1 Introduction and issues 1.1 Germany's structural disadvantages as regards talent recruitment and development in high performance disability sports 1.2 Advantages of foreign systems 2 Overview of the state of research 2.1 International comparison of elite sport funding, taking special account of measures to recruit and develop new talent 2.2 The current controversy between sports scientists and sports practitioners over the structure of talent development in German high-performance sport 2.3 The state of research on high-performance disability sport 3 The special features of high-performance disability sport in the context of talent identification and development 4 Defining the aim and the issues underlying the study 5 The selection of countries 6 The challenges of international comparative research 7 Theoretical frame of reference 8 Methodological procedures 8.1 Research phase 1: document analysis and exploratory interview study 8.2 Research phase 2: online survey 9 Results 9.1 Description of the overall structures of high-performance disability sport in the three countries taking into special consideration the structures of talent identification and development 9.2 Results of the qualitative interview study 9.2.1 Aims 9.2.2 Human Resources 9.2.3 Financial resources 9.2.4 Infrastructural resources, notably in terms of cooperation with schools and rehabilitation centres 9.2.5 Commitments 9.2.6 Evaluation: current challenges and the need for action 9.3 Results of the online survey 9.3.1 Reliability analysis 9.3.2 Regression analysis 9.3.3 Comparison of the quality features across countries 10 Concluding discussion of the results 10.1 The structures of disability sport in the countries under study - a comparison 10.2 Quality features of Talent Identification and Talent Development in the three countries 10.2.1 Comparison of aims 10.2.2 Comparison of human resources 10.2.3 Comparison of financial resources 10.2.4 Comparison of infrastructural resources 10.2.5 Comparison of commitments 10.2.6 Comparison of current challenges 10.3 Investigation of the quality features of Talent Identification and Talent Development in the three countries 10.3.1 Investigation of the internal consistency of ten item batteries 10.3.2 Explanatory factors of the result of talent identification and development 10.3.3 Comparison of the quality features across countries 10.3.4 Country-specific differences at the item level 11 Practical recommendations